2022
DOI: 10.1186/s12889-022-14156-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 lockdowns on physical activity amongst older adults: evidence from longitudinal data in the UK

Abstract: Background A sedentary lifestyle increases the risk of adverse health outcomes and frailty,particularly for older adults. To reduce transmission during the COVID-19 pandemic, people were instructed to stay at home, group sports were suspended, and gyms were closed, thereby limiting opportunities for physical activity. Whilst evidence suggests that physical activity levels reduced during the pandemic, it is unclear whether the proportion of older adults realising the recommended minimum level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
2
15
0
6
Order By: Relevance
“…However, evidence from other research has suggested that deprivation was not a determinant of PA during the pandemic ( 51 ). In fact, changes in PA were more likely related to pre pandemic activity levels, with those who were most active prior to restrictions seeing the greatest reduction in PA during lockdown ( 52 ). However, we did not find this association in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence from other research has suggested that deprivation was not a determinant of PA during the pandemic ( 51 ). In fact, changes in PA were more likely related to pre pandemic activity levels, with those who were most active prior to restrictions seeing the greatest reduction in PA during lockdown ( 52 ). However, we did not find this association in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, using chronological age to characterise individual mortality risk as the basis to implement a blanket policy for older adults at the population level had its problems. Such policies did not take account of the heterogeneity in the pace of ageing among older adults and failed to recognise the consequent harms of physical deconditioning, social isolation, loneliness, depression and decreased quality of life (21)(22)(23) .…”
Section: Biological V Chronological Agementioning
confidence: 99%
“…This very human connectedness and resource for positive ageing has suffered from the pandemic, thus afflicting elders. Elders’ positive ageing, incorporating the maintenance of physical and social life, thus erodes with COVID-19 raging worldwide (Ekoh et al, 2022; Elliott et al, 2022). Boosting or restoring elders’ positive ageing is necessary to terminate the pandemic affliction.…”
Section: Positive Ageingmentioning
confidence: 99%